Case reportPsychodermatologic disorders: case reports and review of literature - Bergler-Czop, Beata; Brzezińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Psychodermatologic disorders are a non-homogenous group, in which both psychological and dermatological components are present. Active co-operation between the dermatologist and the psychiatrist is necessary in all above-mentioned disorders since patients first appear in dermatologic clinics. Dermatological treatment is exclusively symptomatic, since most of all, these patients require special psychiatric treatment, both pharmacological and psychotherapeutic. Here we present three cases of parasitophobia combined with factitial dermatosis and one case of self-injury in patients, in whom diagnosis of psychodermatosis was preceded by long-term and detailed diagnostic procedures for classical dermatological disorders. One should always remember about dermatitis artefacta in patients, in whom there is no positive response to treatment, and the clinical picture as well as results of additional tests comprise no logical whole picture.